Analysis of Socio-Demographic Factors Influencing Anxiety in Hemodialysis Patients - Anggraini, Merry Tiyas; Susilo Budi Pratama (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Advanced chronic kidney disease patients need hemodialysis, the most used method of renal replacement therapy today. The patient will receive hemodialysis therapy for the rest of their life so that it can have a psychological effect like anxiety. Aims: This study aims to examine the socio-demographic variables affecting anxiety in hemodialysis patients. Method: This research used a cross-sectional analytical observational study design. A total sampling technique was used in this research. From 113 outpatient hemodialysis patients in March 2023, 80 samples of patients at Roemani Semarang Hospital met the inclusion and exclusion criteria. Inclusion criteria were patients undergoing hemodialysis at Roemani Semarang Hospital who were willing to participate in the study. Exclusion criteria were incomplete questionnaires, patients with impaired consciousness, patients with communication disorders, and patients using anti-anxiety medication. The information collected was primary information from questionnaires and interviews. The data were tested using the Spearman test with a significance level of p<0.05 for age and family support, and the chi-square test for gender, employment, and educational status. Results: The statistical analysis showed a p-value of 0.704 for age, a p-value of 0.020 for gender, a p-value of 0.558 for employment, a p-value of 0.138 for educational level, and a p-value of 0.000 for family support. Conclusion: The results showed a significant relationship between gender and family support with anxiety levels. The higher the family support, the lower the anxiety level. There is no relationship between age, employment, and education level with the anxiety level of patients undergoing hemodialysis at Roemani Semarang Hospital.